2015
DOI: 10.1186/s13063-015-0944-2
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation (rTMS) for the cognitive rehabilitation of traumatic brain injury (TBI) victims: study protocol for a randomized controlled trial

Abstract: BackgroundRepetitive Transcranial Magnetic Stimulation (rTMS) has been proposed as a new tool in neurological rehabilitation of victims of traumatic brain injury (TBI). However, its usefulness to treat this condition has never been tested rigorously. The primary goal is to conduct a study protocol to determine whether rTMS used to cognitive rehabilitation of victims of TBI with diffuse axonal injury (DAI) is a safe instrument and if it enhances cognitive function recovery.MethodsDouble-blind randomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“… 64 Some studies have found cognitive improvements after rTMS. 66 Transcranial direct current stimulation is another therapy for TBI rehabilitation based on brain excitability modulation via low-amplitude (0.5–2 mA) direct current through the scalp, and Demirtas-Tatlidede et al demonstrated its role in the facilitation of several cognitive domains. 67 …”
Section: Discussionmentioning
confidence: 99%
“… 64 Some studies have found cognitive improvements after rTMS. 66 Transcranial direct current stimulation is another therapy for TBI rehabilitation based on brain excitability modulation via low-amplitude (0.5–2 mA) direct current through the scalp, and Demirtas-Tatlidede et al demonstrated its role in the facilitation of several cognitive domains. 67 …”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, more new relevant studies assessing the effectiveness of non-invasive brain stimulations have been published or are conducting. [ 17 22 ] With the newly published studies and more patients participating in the researches, we are likely able to confirm the effectiveness of non-invasive brain stimulations. In addition, the existing systematic reviews only conducted the pairwise meta-analysis to compare the efficacy of different types of non-invasive brain stimulations by head-to-head.…”
Section: Introductionmentioning
confidence: 96%
“…The use of virtual reality (VR) technology which involves audio and visual stimulations that engage different components of impairment such as memory, attention, and visual perception greatly improves patients’ participation in training and rehabilitation. The use of computer technology has been shown to have advantages for assessment and training of cognitive impairment compared with cognitive training by rehabilitation therapists [ 63 ].…”
Section: Introductionmentioning
confidence: 99%